The Positive Impacts of Employment-Based Contingency on the Treatment of Individuals with Substance Use Disorder: A Systematic Review - Nkechinyere Mary Harry; Ibrahim Folorunsho; Nnenna Okafor; Oluwatosin Arubuolawe; Gibson Anugwom (Disease and Health Research: New Insights Vol. 4, 2024)
Background and Objective: Substance use disorders (SUD) remain a major public health concern and represent a significant cause of morbidity and mortality. Given the growing need for society to address this issue of SUD, it is essential to identify effective solutions to the problems this crisis poses to people’s lives, health, and socioeconomic well-being. These social welfare issues are particularly affecting minority populations, who face disproportionately high levels of marginalization and disparities in healthcare. Aim: The goal of this study is to explore and determine the effects of employment-based contingency (EBC) on enrolling SUD individuals into treatment, the rate of treatment adherence, and the rate of post-treatment abstinence. Methods: PubMed and Google Scholar search was conducted using the search terms ((substance use disorder) AND (unemployment)) OR (therapeutic workplace)), for randomized controlled trials (RCT) published between 2012 and 2022, reporting on participants between ages 18 and 65 years who use opioids, cocaine or alcohol. Results: Seven RCTs met the inclusion criteria, with a total of 389 participants. Three RCTs involving 203 participants found that EBC positively impacted treatment enrollment rates, with 100%, 92%, and 100% enrollment in the respective studies. Three articles involving 172 participants found a higher rate of treatment adherence and retention to treatment among EBC participants compared to the control group. There was more naltrexone-positive urine in the EBC group compared to control (72% vs. 21%, with a p-value of .01), and 74% (EBC) vs 26% (control) participants completed treatment. Four articles with 238 participants found that EBC improved the rate of abstinence by over 50%, which is double the rate among the control group without EBC. However, in three articles with 204 participants, EBC participants and control groups exhibited an equal rate of drug abstinence during the post-intervention period, further suggesting no significant difference in the rate of abstinence between the groups. Conclusion: EBC is effective in improving SUD treatment enrollment, treatment adherence, and post-treatment abstinence, however, the efficacy may vary depending on how much is earned as an incentive. This policy is likely to be more successful with the strong support of employers in both the private and public sectors and the provision of support such as funding for businesses willing to implement these measures in their workplace for individuals with SUD.